Tinjauan Yuridis Tentang Keabsahan Pengalihan Kredit Pemilikan Rumah (KPR) Bawah Tangan Sebagai Dasar Balik Nama Sertifikat Tanah Dan Bangunan - Nadia Viranita; Tjempaka Tjempaka (Jurnal Interpretasi Hukum, 2025)
This study examines the legal validity of transferring a mortgage (Kredit Pemilikan Rumah/KPR) through an informal over-credit agreement and its implications for land certificate registration in Indonesia. In practice, many home buyers continue mortgage installments under private agreements with the original debtor, without obtaining approval from the bank or executing a notarial deed. Such arrangements often create legal uncertainty, particularly when the original debtor becomes unreachable, making it impossible to complete the formal process of certificate transfer. The case of the Cibinong District Court Decision No. 324/Pdt.G/2023/PN Cbi illustrates this problem. The plaintiff, who had fully paid the mortgage installments, requested the court to declare the over-credit agreement valid and to order the bank and the land office to transfer the certificate. However, the court rejected the claim, emphasizing that private over-credit agreements contradict banking regulations and agrarian law, which require both creditor approval and an authentic deed before registration can be made. This decision highlights the importance of formal procedures in land and mortgage transactions to ensure legal certainty.